Techno-economic study on implementation of inventory control requirements for a nuclear powered closed-cycle gas turbine power plant - Osigwe, Emmanuel O.; Gad-Briggs, Arnold; Obhuo, Mafel; Pilidis, Pericles (ASME, 2020)
The use of an inventory control system offers a unique benefit of stable cycle thermal efficiency during part-load operation. This article focuses on the influence of initial inventory tank pressure on the control level using pressure differential as a driving force of the inventory control system. The study also considered the effects of using multiple tanks to increase the overall size of the inventory control tank and the use of insulation to reduce the impact of temperature variation between the compressor discharge temperature and the inventory tank temperature. The second part of this analysis is a cost comparison between the use of multiple tanks and the use of a transfer compressor to achieve high cycle efficiency at continuous part-load operation. The discussions in this paper accentuate the optimum benefit for utilizing an inventory control system for a single-shaft intercooled-recuperated closed-cycle gas turbine plant
Keywords: Thermal efficiency; Insulation; Stress; Pressure; Compressors; Power stations; Closed-cycle gas turbines